FEMINIST APPROACH IN ANN BRASHARESÃ¢â¬â¢S THE SISTERHOOD OF THE TRAVELING PANTS - Purwanto, Bambang (Language Circle: Journal of Language and Literature, 2009)
The purpose of this writing is to express that friendship is more important than hostility. The reason of hostility is annoyance, emotion and lack of patience in facing problems. The effect of it is the destruction of friendship and the increase in annoyance among them. Feminist is a method that is used in this writing. The application of this method is to express that man and woman have the right to make their own decisions. Both of them will respect and understand. They will have responsibility for everything they have done. This method is also expressing that human have freedom in their life. In this novel, there are four women. They are Carmen, Bridget, Lena and Tibby. The four of them spend their summer holiday into different places. In their summer holiday, they have experienced incidents which can destroy friendship. Carmen hates her father, Lena hates Kostos, Bridget hates Eric and Tibby hates Bailey. Finally, they realize that annoyance between them can destroy their friendship. The writer used Feminist approach because the main characters wanted to destroy the patriarchy of man. They insist that man can respect womanÃ¢â¬â¢s opinion. ÃÂ  Key words: Friendship, Conflict, Respect